2011
DOI: 10.1007/s12011-011-9176-9
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Fibroblast Proliferation by Insoluble Gadolinium Salts

Abstract: The purpose of this study was to assess insoluble salts containing gadolinium (Gd3+) for effects on human dermal fibroblasts. Responses to insoluble Gd3+ salts were compared to responses seen with Gd3+ solubilized with organic chelators, as in the Gd3+-based contrast agents (GBCAs) used for magnetic resonance imaging. Insoluble particles of either Gd3+-phosphate or Gd3+-carbonate rapidly attached to the fibroblast cell surface and stimulated proliferation. Growth was observed at Gd3+ concentrations between 12.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…Since gadolinium rapidly forms insoluble precipitates with phosphate, carbonate, and other anions in biological fluids [32], experiments were conducted in which a chelated gadolinium compound (Magnevist; i.e., gadolinium diethylenetriaminepentaacetic acid N -methylglucamine) was used in place of gadolinium chloride. Similar to what we observed with gadolinium chloride, the chelated gadolinium compound (250 and 500 µM) induced a decrease in the number of colon epithelial cells when combined with millimolar amounts of calcium (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since gadolinium rapidly forms insoluble precipitates with phosphate, carbonate, and other anions in biological fluids [32], experiments were conducted in which a chelated gadolinium compound (Magnevist; i.e., gadolinium diethylenetriaminepentaacetic acid N -methylglucamine) was used in place of gadolinium chloride. Similar to what we observed with gadolinium chloride, the chelated gadolinium compound (250 and 500 µM) induced a decrease in the number of colon epithelial cells when combined with millimolar amounts of calcium (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that gadolinium interferes with receptor-gated calcium channels, as well as voltage-gated and mechanical stress-activated channels in a variety of cells [22, 24, 36, 37]. While some studies have suggested that limiting the rise in intracellular calcium might prevent apoptosis and promote cancer development, most studies have demonstrated that blocking calcium movement into the cell induces cell death [reviewed in 32]. In the colon epithelial cells studied here, interference with calcium movement is clearly associated with reduced cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Once phagocytosed, Omniscan ® would be able to amplify its TLR signaling capacity by engaging TLR7 within the endosome. Several reports of Gd deposits found in affected tissues from NSF patients described the presence of macrophages in close proximity (912), suggesting that the highly acidic environment of the endosome could facilitate deposition of Gd salts, such as Gd phosphate and Gd carbonate (49). These precipitated Gd salts could then maintain a constant state of TLR activation in both macrophages and fibroblasts, producing a chronic proinflammatory/profibrotic phenotype responsible for disease persistence and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Linear GBCAs have higher dissociation rates than macrocyclic GBCAs; the resulting free Gd may bind to endogenous molecules such as phosphate, carbonate or macromolecules, leading to Gd retention in various tissues. 10,11 In the unchelated form, Gd is highly toxic and may cause splenic and lung degeneration or liver necrosis.…”
Section: Introductionmentioning
confidence: 99%